Exergoeconomic analysis and optimization of single-pressure single-stage and multi-stage CO2 transcritical power cycles for engine waste heat recovery: A comparative study. (1st January 2018) - Wang, Shun-sen; Wu, Chuang; Li, Jun
Abstract: The present work mainly focuses on the thermodynamic and exergoeconomic comparisons between the novel single-pressure multi-stage CDTPCs (carbon dioxide transcritical power cycles) and single-pressure single-stage CDTPC for engine waste heat recovery. A method based on exergy fuel distribution is proposed to calculate the fuel cost for the bottoming CDTPCs. Parametric analysis is conducted to study effects of the decision variables on the performances of the considered CDTPCs, which are also optimized and compared. The thermodynamic study shows that the double-stage CDTPC can produce the highest net power output of 517.27 kW for a 2928 kW engine at exhaust gas temperature of 470 °C. The exergoeconomic study reveals that the single-stage CDTPC has the lowest total unit cost when exhaust gas temperature is 300–600 °C and the double-stage CDTPC is recommended when exhaust gas temperature is 530–600 °C due to better thermodynamic and exergoeconomic performances. Meanwhile, the triple-stage CDTPC is not recommended when exhaust gas temperature is 300–600 °C considering thermodynamics and exergoeconomics. A multi-objective optimization is also conducted to obtain an optimal condition for the considered CDTPCs for the case study. Graphical abstract: Image 1 Highlights: 1. A method based on exergy fuel distribution is proposed to calculate the fuel cost. 2. Exergoeconomic analysis is performed for multi-stage CO2 transcritical power cycles. 3. Single-stage CO2 power cycle has lowest total product unit cost. 4. Double-stage CO2 power cycle is preferable when exhaust temperature is ≥ 530 °C.